Investigation of recycled materials in hot-mix asphalt mixtures - Gao, Ya (Kansas State University, 2024)
In the United States, asphalt, concrete, aggregates, and other materials are used in large quantities to build highway pavements. Hot-mix asphalt (HMA) mixtures typically contain approximately 93-96% aggregates and 4-7% asphalt binder. Recycled materials can replace these two main components, which provide economic and environmental benefits. However, the recycled materials affect the properties of asphalt cement and HMA mixture and, in turn, the durability of asphalt pavements. Thus, evaluating HMA containing recycled materials is a significant research pursuit. This study investigated the performance of HMA mixtures containing carbon char and fly ash. The rheological properties of Recycled Engine Oil Bottom (REOB) blended binders were also investigated. Finally, research was done to determine recycled asphalt pavement (RAP) content in HMA during production in the drum mix plants. Results showed that small quantities of carbon char can improve moisture resistance but reduce rutting resistance. Adding about 15% fly ash to the asphalt binder would perform similarly in rutting, fracture cracking, and moisture susceptibility to the HMA mixture without fly ash. No interaction between the recycled material and the asphalt binder was apparent in both cases. A hand-held XRF spectrometer can detect some of the “signature” elements present in REOB. The addition of REOB reduced the binder stiffness at high temperatures and improved the low-temperature properties. The theoretical RAP quantities in the produced HMA mix in drum mix plants varied due to differences in the RAP burn-off test results between the labs in the QC/QA process. More frequent RAP binder determination was suggested for better process control of input RAP quantity in the mix production process. Using recycled materials in HMA mixtures looks enticing due to increasing environmental awareness and the need for sustainable construction practices. However, carefully selecting and managing recycled materials are needed to achieve sustainable and cost-effective road construction practices while meeting performance requirements. The fundamental interaction between recycled material and asphalt binders should be studied first to ensure the role of recycled materials. The QC/QA process during HMA production using RAP should be enhanced since the input RAP properties determine the RAP quantity being used and should be within a specified limit.
Keywords: Hot-mix asphalt mixture; Recycled material; Asphalt binder; Quality control and quality assurance